2007
DOI: 10.1016/j.paid.2007.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the reliability and factor structure of the Autism Spectrum Quotient (AQ) in a non-clinical sample

Abstract: A self-report screening measure for high functioning autism spectrum disorders is needed for diagnostic screening and research purposes. The Autism Spectrum Quotient (AQ) has been developed for these reasons, although a comprehensive assessment of the psychometric properties of the AQ has not been completed. The purpose of the current study was to assess the distribution, internal consistency, and factor structure of the AQ in a non-clinical sample (n = 1005). The current findings demonstrate the normal distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
171
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(200 citation statements)
references
References 11 publications
27
171
2
Order By: Relevance
“…In this respect, it is important to consider studies in which the factor analytic structure of the AQ has been examined. Two studies suggested three underlying factors: Social skill, Details/patterns and Communication/mindreading (Austin, 2005;Hurst, Mitchell, Kimbrel, Kwapil, & Nelson-Gray, 2007) and one study suggested a broad Social interaction subscale and a second subscale Attention to detail (Hoekstra et al, 2008). In the three existing factor analytic studies, the subscale Imagination was never established as a separate subscale.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it is important to consider studies in which the factor analytic structure of the AQ has been examined. Two studies suggested three underlying factors: Social skill, Details/patterns and Communication/mindreading (Austin, 2005;Hurst, Mitchell, Kimbrel, Kwapil, & Nelson-Gray, 2007) and one study suggested a broad Social interaction subscale and a second subscale Attention to detail (Hoekstra et al, 2008). In the three existing factor analytic studies, the subscale Imagination was never established as a separate subscale.…”
Section: Discussionmentioning
confidence: 99%
“…While the psychometric properties of the overall scores produced by the AQ have consistently been shown to be reasonably good (Baron-Cohen et al, 2001;Hoekstra, Bartels, Cath, & Boomsma, 2008;Kurita and Koyoma, 2006;Wakabayahi, Baron-Cohen, Wheelwright, and Tojo, 2006), a number of studies have raised concerns regarding the internal consistencies of the five domains detailed in the initial model by Baron-Cohen et al Based on the results of subsequent factor analyses, it has been suggested that, alternatively, the AQ could be more accurately defined by a four- (Stewart & Austin, 2009), three- (Hurst, Mitchell, Kimbrel, Kwapil, & Nelson-Gray, 2007), or two-domain model (Hoekstra et al, 2008). This study utilized the Hoekstra et al (2008) two-domain model comprised of the original 'Attention to Details' factor, and a higher-order factor of 'Social Interaction', which encompasses the Social Skills, Communication, Attention Switching, and Imagination domains from the original Baron-Cohen et al (2001) model.…”
Section: Asd Phenotype Expression: Autism-spectrum Quotient (Aq;mentioning
confidence: 99%
“…The traits associated with the BAP have been described as following a roughly normal distribution within the TD population (Best et al 2008;Hoekstra et al 2007;Hurst et al 2007;Pisula et al 2015). Young adults with higher levels of the BAP are similar to those with ASD in that they have been shown to struggle more with loneliness, creating and maintaining friendships (Jobe and White 2007), depression, anxiety, and being victims of bullying (Kunihira et al 2006).…”
Section: The Broad Autism Phenotypementioning
confidence: 99%
“…It has also been used to assess these traits in TD populations (e.g., Hurst et al 2007;Jobe and White 2007;Kunihira et al 2006). Example items on the AQ include: "I find it difficult to work out people's intentions" and "I am fascinated by numbers."…”
Section: Autism Spectrum Quotientmentioning
confidence: 99%